Cholecystocholangiography in patients with symptomatic gallstones. A prospective, randomized, controlled trial (Revista Argentina de Cirugía, 2021)
Background: the laparoscopic technique is most often used for cholecystectomies. Although it is recommended to always include a transcystic intraoperative cholangiography (CTC), few surgeons comply because this procedure requires more experience and technical skill. If the CTC could be replaced by a simpler technique, as transvesicular cholangiography (CTV), adherence to the recommendation could be increased. The aim of this study was to compare the quality of transvesicular cholangiography with regards to transcystic cholangiography.Method: patients were randomized into 2 groups, CTV and CTC. We analyzed: image quality, success rate, conversion of cholangiography technique, operative time, duration of cholangiography, fluoroscopy time, amount of radiation received and amount of contrast injected. Data were analyzed using chi-square and Mann-Whitney Test or Student t test. A p < 0.05 was considered significant.Results: the success rate of CTV vs. CTC was 91.4% vs. 94.1%. (p > 0.05). In the CTV group, this technique could not be performed in 7.1% of patients. The duration of the procedure was 5 min 36 s vs. 10 min 58 s (p < 0.0001) for CTV vs. CTC, respectively. Fluoroscopic exposure time, amount of radiation and total duration of surgery showed no significant difference between groups. The amount of contrast used was 22.5 mL vs. 8.5 mL (p < 0.0001) for CTV vs. CTC, respectively.Conclusion: since image quality and success rate of transvesicularcholangiography were comparable to transcystic cholangiography, with no differences in the duration and amount of radiation, we suggest that transvesicular technique could be used as a
Keywords: intraoperative cholangiography; cholecystocholangiography; transcystic cholangiography; laparoscopic cholecystectomy